THE MAKING OF RICE BRAN FLOUR-BASED SOURDOUGH BREAD - Ardhia Deasy Rosita Dewi; Arnold Tjahjono (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2022)
Sourdough is a bread made with the involvement of Lactobacillus bacteria and yeast that are naturally present in wheat flour. This study used rice bran and milk kefir grains to speed up the preparation of starters. Rice bran is used to reduce gluten content in bread as well as add nutritional value to bread. This research aims to determine the impact of the concentration of rice bran flour (0, 25, and 50% w/w of total flour) on the physical, chemical, and organoleptic parameters of sourdough. An increase in the rice bran flour concentration leads to an increase in the pH, hardness and brittleness of the bread. Besides, it also causes a decrease in lactic acid levels and bread expansion volume which makes the bread taste less sour. The results of the organoleptic analysis showed that sourdough with a concentration of 25% rice bran flour was the most preferred bread, as it is less sweet, without sour and bitter taste and a little bit salty. Moreover, it has a less unpleasant aftertaste, non-sour aroma, brown colour and it is not too soft in texture.